(untitled) (Bangladesh Journal of Medical Science, 2024)
Background Usually umbilical hernia contains bowel loops and omentum. The diagnosis becomes even more challenging when they imitate strangulated umbilical hernia. An acutely inflamed appendix has been seen in the femoral and inguinal hernia but is rarely found in the paraumbilical hernia. Objectives To observe the symptoms, findings, and treatment process of cases of umbilical/ paraumbilical hernia in past literature and document a case report in the appendix within the paraumbilical hernia. Methods Literature has been searched with keywords and statements of umbilical hernia, appendix within the umbilical hernia, and paraumbilical hernia. Studies on appendix within paraumbilical hernia are scarce in the literature. Six studies from the past 12 years were included. Results There were six studies included. Pain, fever, vomiting, and swelling on the umbilicus were the common symptoms. No postoperative complication was seen. Conclusion Several factors can be responsible for umbilical hernia. A case report of a 50-years old male presented to Jinnah Hospital, Lahore with pain and umbilical swelling. Appendiceal inflammation was found in the hernia sac. Umbilical herniorrhaphy and appendectomy were done. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 309-313